Environmental risk assessment using FMEA and entropy based on TOPSIS method: a case study oil wells drilling - Negar Afzali Behbahani; Mazdak Khodadadi-Karimvand; Afarin Ahmadi (Big Data and Computing Visions)
Drilling is among the major processes of exploration, description, and development of oil and gas reservoirs with a strategic significance in the oil industry. It has also always been a major challenge in the oil industry. Because of the importance of drilling in major upstream oil and gas industries, identifying related risks is also of great importance. Risk assessment systems are tools for identifying potential risks and assessing their levels, which have been widely used in various industries and disciplines in recent years. Accordingly, this study identified and assessed major environmental risks caused by onshore and offshore drilling operations and presented an approach to reduce their risk levels. Offshore and onshore risks were identified after identifying the drilling operation of oil wells. Indexes used in the FMEA method were selected to determine the most significant risks. The identified risks were then ranked by experts and entered the TOPSIS decision matrix as a useful technique to prioritize and select the most significant and most effective risks. Shannon's Entropy was used to weight identified indexes. Finally, 33 environmental risks resulting from oil well drilling operations in onshore and offshore ecosystems were identified. Corrective measures were presented for each environment to reduce the level of identified risks and their effect on the environment.